Children left behind in China: The role of school fees - Hai-Anh Dang; Yang Huang; Harris Selod (IZA Journal of Development and Migration, 2020)
The barriers faced by Chinese rural-urban migrants to access social services, particularly education, in host cities could help explain why the majority of them choose to leave their children behind. We identified the causal impacts of school fees by instrumenting for it with unexpected shocks to the city's public education spending. Our findings suggest that higher fees deter migrant workers from bringing their children with them, especially their daughters, reduce the number of children they bring, and increase educational remittances to rural areas for the children left behind. Increases in school fees mostly affect vulnerable migrant workers and could have stronger impacts during an economic crisis. These findings hold for different model specifications and robustness checks.
Keywords: I22; J61; O15; 330; child migration; school fees; public education spending; urbanization; China